Perceived Benefits as Variable Related to Voluntary Enrolment in the National Health Insurance Program (JKN) at Public Health Centre I East Denpasar - Ida Ayu Putri Widhiastuti; Pande Putu Januraga; Dewa Nyoman Wirawan (Universitas Udayana, 2015)
Background and purpose: By 2019 all Indonesian citizens should be covered by the JKN program. In 2015 the proportion of population covered by JKN was 53.4%, constituting 34.0% paid by the government, 4.3% by their employer and 3.9% independently, while 57.8% were not covered by JKN. In order to achieve universal coverage there needs to be increased enrolment from non-government employees and people who work independently. This study aims to understand the relationship between out patient enrolment and sociodemographic variables, information about JKN, perceived risk of falling sick, perceived benefits and barriers to access JKN. Methods: Cross sectional sample survey was conducted among 188 households, consist of 94 non-employee JKN participants and 94 respondents not yet enrolled. Data was collected through interview and analyzed by univariate, bivariate and multivariate analysis using logistic regression. Results: Exposure to JKN information was 89.36%. Bivariate and multivariate analysis showed that the only variable associated with JKN enrollment was perceived benefits with adjusted OR=4.53 (95%CI: 2.15-9.55). There was no association with sociodemographic variables, information regarding JKN and health status risk perception. Conclusion: Variable connected with voluntary JKN enrolment at Primary Health Care I Denpasar East was perception of benefits.